Investigating traffic fatality trends and restraint use among rear-seat passengers in the United States, 2000–2016. (June 2020) - Li, Amy; Shen, Sijun; Nwosu, Ann; Ratnapradipa, Kendra L.; Cooper, Jennifer; Zhu, Motao
Highlights: Research on epidemiologic patterns of rear-seat passenger fatalities is limited. The overall rear-seat passenger fatality rate has decreased 44% between 2000 and 2016. The fatality rate among rear-seat passengers had decreased more in males than females, and also decreased more in passengers aged 14–19 years than in other age groups. Fatally injured male rear-seat passengers were more likely to be unrestrained than females, and both the youngest (≤13 years) and oldest (65–85 years) passengers were less likely to be unrestrained than those aged 20–64 years. Abstract: Introduction: Motor-vehicle crash is one of the leading causes of unintentional injury death in the United States. Previous studies focused on fatalities among drivers and front-seat passengers, with a limited number of studies examining rear-seat passenger fatalities. The objectives of this study were to assess trends in rear-seat passenger motor-vehicle fatalities in the United States from 2000 to 2016 and to identify demographic factors associated with being unrestrained among fatally injured rear-seat passengers. Methods: Rear-seat passenger fatality data were obtained from the Fatality Analysis Reporting System (FARS) database. The fatality rate ratios for overall rear-seat passengers and for different age and sex groups were determined by comparing fatality rates in 2000 and 2016 using random effects models. Risk ratios of being unrestrained for age and sex groups were obtained using general estimating equations. Results: Compared to 2000, the overall rear-seat passenger fatality rate in 2016 decreased by 44% (95% confidence interval [CI]: 39–49%). In particular, the fatality rate among rear-seat passengers decreased more in males than females, and passengers aged 14–19 years experienced a larger decline than all other age groups. Fatally injured male rear-seat passengers had a higher risk of being unrestrained (adjusted risk ratio: 1.06, 95% CI: 1.04–1.07) than their female counterparts, and both youngest (≤13 years) and oldest (65–85 years) passengers were less likely to be unrestrained than those aged 20–64 years. Conclusions: Overall, fatality rates among rear-seat passengers have declined, with differential degrees of improvement by age and sex. Practical Applications: Continued restraint use enforcement campaigns targeted at teenagers and males would further preserve them from fatal injuries and improve traffic safety for the overall population.